An Integrated Account of Phonological Weakening Processes in English within Optimality Theory - 최재혁 (English Language and Linguistics, 2015)
The analysis of weakening phenomena may vary according to the theory you adopt and the language you choose, but in this study, vowel reduction and consonant lenition in the history of English will be explored in a constraint-based approach. In addition, most importantly, I seek to show which generalisations can equally be applied to both consonant lenition and vowel reduction in terms of a phonological theory. In this regard, I suggest a unified theoretic account of weakening phenomena involving the combination of two approaches namely Element Theory (e.g., Harris 1994, Backley 2011) and Optimality Theory (Prince and Smolensky 1993), which differentiates this account from previous analyses. I argue that the *COMPLEX[Element] constraint family, where ‘element’ refers to one of the primitives of Element Theory, plays a central role in analysing phonological weakening processes in English. In addition, it will be shown that both consonant lenition and vowel reduction can be accounted for within the constraint interaction between positional faithfulness constraints such as IDENT[Element] and the integrated constraint *COMPLEX[Element] which I propose. KCI Citation Count: 0